The Effects of Differentially-Expressed Homeobox Family Genes on the Prognosis and HOXC6 on Immune Microenvironment Orchestration in Colorectal Cancer - Qi, Lina; Ye, Chenyang; Zhang, Ding; Bai, Rui; Zheng, Shu; Hu, Wangxiong; Yuan, Ying (Frontiers in Immunology, 2021)
Background The homeobox (HOX) gene family encodes highly conserved transcription factors, that play important roles in the morphogenesis and embryonic development of vertebrates. Mammals have four similar HOX gene clusters, HOXA, HOXB, HOXC, and HOXD, which are located on chromosomes 7, 17,12 and 2 and consist of 38 genes. Some of these genes were found to be significantly related to a variety of tumors; however, it remains unknown whether abnormal expression of the HOX gene family affects prognosis and the tumor microenvironment (TME) reshaping in colorectal cancer (CRC). Therefore, we conducted this systematic exploration to provide additional information for the above questions. Methods RNA sequencing data from The Cancer Genome Atlas (TCGA) and mRNA expression data from Gene Expression Omnibus (GEO) combined with online tumor analysis databases (UALCAN, TIMER, PrognoScan) were utilized to explore the relationship among abnormal expression of HOX family genes, prognosis and the tumor immune microenvironment in CRC. Results 1. Differential expression and prognosis analysis: 24 genes were significantly differentially expressed in CRC compared to adjacent normal tissues, and seven upregulated genes were significantly associated with poor survival. Among these seven genes, univariate and multivariate Cox regression analysis revealed that only high expression of HOXC6 significantly contributed to poor prognosis; 2. The influence of overexpressed HOXC6 on the pathway and TME: High HOXC6 expression was significantly related to the cytokine pathway and expression of T cell attraction chemokines, the infiltration ratio of immune cells, expression of immune checkpoint markers, tumor mutation burden (TMB) scores and microsatellite instability-high (MSI-H) scores; 3. Stratified analysis based on stages: In stage IV, HOXC6 overexpression had no significant impact on TMB, MSI-H, infiltration ratio of immune cells and response prediction of immune checkpoint blockers (ICBs), which contributed to significantly poor overall survival (OS). Conclusion Seven differentially expressed HOX family genes had significantly worse prognoses. Among them, overexpressed HOXC6 contributed the most to poor OS. High expression of HOXC6 was significantly associated with high immunogenicity in nonmetastatic CRC. Further research on HOXC6 is therefore worthwhile to provide potential alternatives in CRC immunotherapy.